Crystal structure and phase composition evolution during heat treatment of Fe-45Ga alloy. (April 2021) - Vershinina, T.N.; Bobrikov, I.A.; Sumnikov, S.V.; Boev, A.O.; Balagurov, A.M.; Mohamed, A.K.; Golovin, I.S.
Abstract: The atomic structure of the high-temperature β-Fe6 Ga5 phase, formed in the Fe-45at.%Ga alloy during rapid cooling from the melt, has been refined by X-ray, neutron diffraction techniques, and density functional theory calculations. The regularities of the phase composition evolution of the quenched Fe-45at.%Ga alloy in the process of continuous slow heating and cooling under vacuum conditions have been revealed. It is shown that after the heating-cooling cycle, the structures of the outer layers and the sample volume are completely different. Highlights: Atomic structure of the high-temperature β-Fe6 Ga5 phase has been studied. Different phase composition of the inner volume and the outer layer was fixed by the ND and XRD. Elemental composition of the surface layer changes due to gallium evaporation.